Natural Presentation of Glycosaminoglycans in Synthetic Matrices for 3D Angiogenesis Models - Zapp, Cornelia; Mundinger, Patricia; Boehm, Heike (Frontiers in Cell and Developmental Biology, 2021)
Glycosaminoglycans (GAGs) are long, linear polysaccharides that occur in the extracellular matrix of higher organisms and are either covalently attached to protein cores, as proteoglycans or in free form. Dependent on their chemical composition and structure, GAGs orchestrate a wide range of essential functions in tissue homeostasis. Accordingly, GAG-based biomaterials play a major role in tissue engineering. Current biomaterials exploit crosslinks between chemically modified GAG chains. Due to modifications along the GAG chains, they are limited in their GAG-protein interactions and accessibility to dissect the biochemical and biophysical properties that govern GAG functions. Herein, a natural presentation of GAGs is achieved by a terminal immobilization of GAGs to a polyethylene glycol (PEG) hydrogel. A physicochemical characterization showed that different end-thiolated GAGs can be incorporated within physiological concentration ranges, while the mechanical properties of the hydrogel are exclusively tunable by the PEG polymer concentration. The functional utility of this approach was illustrated in a 3D cell culture application. Immobilization of end-thiolated hyaluronan enhanced the formation of capillary‐like sprouts originating from embedded endothelial cell spheroids. Taken together, the presented PEG/GAG hydrogels create a native microenvironment with fine-tunable mechanobiochemical properties and are an effective tool for studying and employing the bioactivity of GAGs.